(untitled) (Journal of Imam Al-Kadhim College, 2025)
The concepts of enlightenment, renewal, and globalization should take on a new form that suits the modern age to curb those who deny religious constants, who are interested in succumbing to the allure of life and its pleasures, which Islam has not absolutely forbidden but has surrounded with a bracelet that ensures human happiness and frames it within the framework of purity, chastity, and social cohesion. Modernists today call for renewal, but in reality, they are reviving the opinions of those who witnessed the dawn of Islam and are adopting their views that were established by God Almighty in the verses of the Quran. They call for the abolition of the sanctity of the Holy Quran by seeking to prove its humanity and thus instill the possibility of deficiency and flaws in it and in the minds of the young, then questioning the revelation to break trust in the sanctity of the Quranic text, and then questioning the Messenger. That is, doubts extend to the message, the Messenger, and the Sender. Their proofs are only from the inspiration of their thoughts that are prone to error, deficiency, and confusion. Where are those who were witnessed by people for their truthfulness, honesty, and integrity, and their Creator testified to that by saying, "Invite to your Lord, for you are surely on a straight path" (Al-Hajj: 67)? If there were any deficiency or moral flaw in his person, it would have been established among his contemporaries, knowing that what the deniers of the sanctity of the Holy Quran claim and their objection to the Prophet is the same thing that the Holy Quran established about them in its verses.